Peningkatan Kinerja UMKM dengan Keunggulan Produk Inovatif - Natasha Anggraini, Sherly; Ida Puspitowati (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
The purpose of this study is to analyze the role of innovative product excellence in mediating entrepreneurial orientation and dynamic capabilities that determine the business performance of Bakery MSMEs in Tangerang Regency. By using entrepreneurial orientation and dynamic capabilities as independent variables, business performance as the dependent variable and innovative product advantage as a mediator to analyze the role of innovative product advantage. This research method uses quantitative with descriptive research design. The sample was carried out using the purposive sampling method. Of the 200 complete questionnaires, 80 data were declared eligible for analysis. Data analysis used the PLS-SEM method through SmartPLS 4.0 software. The results of this study indicate that entrepreneurial orientation has a positive and significant influence on business performance, as well as a positive and significant influence on innovative product advantage. Dynamic capabilities have a positive and significant influence on business performance, as well as a positive influence on innovative product advantage. Furthermore, innovative product advantage has a positive influence on business performance. The mediator’s results show that innovative product advantage mediates the influence of entrepreneurial orientation on business performance. Innovative product advantage is also able to mediate dynamic capabilities on the business performance of Bakery MSMEs in Tangerang Regency. The conclusion of this study shows that improving the performance of bake shop MSMEs can be achieved through strengthening entrepreneurial orientation and dynamic capabilities which are manifested in the creation of innovative product advantage. Keywords: Business Performance, Dynamic Capabilities, Entrepreneurial Orientation, Innovativeness Roduct Advantage